Employment outcomes and patterns of real estate graduates: is gender a matter?. Issue 1 (15th February 2016) - Poon, Joanna; Brownlow, Michael
Abstract : Purpose: – The purpose of this paper is to investigate whether gender has an impact on real estate and built environment graduates' employment outcomes, employment patterns and other important employment related issues, such as pay, role, contract type and employment opportunity in different states of a country. Design/methodology/approach: – The data used in this paper has been collected from the Australian Graduate Survey (AGS). Data from the years 2010-2012 was combined into a single data set. Dimensionality reduction was used to prepare the data set for the courses listed in AGS data, in order to develop the simplified classifications for real estate and built environment courses which are used to conduct further analysis in this paper. Dimensionality reduction was also used to prepare data set for the further analysis of the employment outcomes and patterns for real estate graduates. Descriptive and statistical analysis methods were used to identify the impact of gender on the employment outcomes, employment patterns and other important employment related issues, such as pay, role, contract type and location of job, for real estate graduates in Australia. This paper also benchmarks the employment result of real estate graduates to built environment graduates. Findings: – Recent male built environment graduates in Australia are more likely to gain full-time employment than females. The dominant role for recent female built environment graduates in Australia is a secretarial or administrative role while for the male it is a professional or technical role. Male real estate and built environment graduates are more likely to have a higher level of salary. Gender also has an impact on the contract type. Male built environment graduates are more likely to be employed on a permanent contract. On the other hand, gender has no impact on gaining employment in different states, such as New South Wales and Queensland, in Australia. The finding of this paper reinforces the view of previous literature, which is that male graduates have a more favourable employment outcomes and on better employment terms. The finding also shows that graduate employment outcomes for real estate and built environment graduates in Australia are similar to that in other countries, such as the UK, where equivalent studies have been published. Originality/value: – This is pioneering research that investigates the impact of gender on employment outcomes, employment patterns and other employment related issues for real estate graduates and built environment graduates in Australia.